Sexual and reproductive decision-making of university students in Cali and Palmira: some associated factors - Enciso Múnera, Natalia (Universidad Pontificia Bolivariana, 2020)
Following the model proposed by Trujillo, Henao & González (2007), based on narratives obtained through in-depth interviews, in this investigation, some of the factors that can influence sexual and reproductive decision making in university students were identified. The life stories of 4 women and 2 men from the cities of Cali and Palmira, about their processes of sexual socialization, allowed us to identify how knowledge, norms, beliefs, attitudes, valuations and meanings constructed in the sociocultural context guide and intervene in their decisions about the different ways of living sexuality.  Among the most relevant findings of this investigation we found that the sociocultural context in which subjects live issues related to sexuality has not changed substantially in recent years.This leads to questioning the role of sex education as a relevant and effective factor for the purpose of guaranteeing the sexual and reproductive health of these populations.